2009
DOI: 10.1200/jco.2009.24.2446
|View full text |Cite
|
Sign up to set email alerts
|

Phase III Randomized Comparison of Gemcitabine Versus Gemcitabine Plus Capecitabine in Patients With Advanced Pancreatic Cancer

Abstract: On the basis of our trial and the meta-analysis, GEM-CAP should be considered as one of the standard first-line options in locally advanced and metastatic pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
408
2
20

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 713 publications
(449 citation statements)
references
References 27 publications
19
408
2
20
Order By: Relevance
“…In advanced or metastatic pancreatic cancer, combinations of gemcitabine plus 5-fluorouracil (5-FU) [4], cisplatin [5], oxaliplatin [6] and irinotecan [7] have not shown significant benefit in overall survival compared to single-agent gemcitabine. Capecitabine, an orally administered fluoropyrimidine carbamate which converts to active 5-FU in the tumour site demonstrates efficacy in untreated advanced colorectal carcinoma [8] and the combination of gemcitabine and capecitabine in advanced pancreatic cancer improves overall survival, clinical benefit response and quality of life at a statistically significant level compared with standard gemcitabine treatment [9,10]. Reports of expression of the ErbB receptor family, including the epidermal growth factor receptor (EGFR; ErbB1/HER1) and HER2; ErbB2/neu vary widely in PDAC.…”
Section: Introductionmentioning
confidence: 99%
“…In advanced or metastatic pancreatic cancer, combinations of gemcitabine plus 5-fluorouracil (5-FU) [4], cisplatin [5], oxaliplatin [6] and irinotecan [7] have not shown significant benefit in overall survival compared to single-agent gemcitabine. Capecitabine, an orally administered fluoropyrimidine carbamate which converts to active 5-FU in the tumour site demonstrates efficacy in untreated advanced colorectal carcinoma [8] and the combination of gemcitabine and capecitabine in advanced pancreatic cancer improves overall survival, clinical benefit response and quality of life at a statistically significant level compared with standard gemcitabine treatment [9,10]. Reports of expression of the ErbB receptor family, including the epidermal growth factor receptor (EGFR; ErbB1/HER1) and HER2; ErbB2/neu vary widely in PDAC.…”
Section: Introductionmentioning
confidence: 99%
“…Nineteen studies involving 4697 patients were included (Supplementary Table 2) (Berlin et al, 2002;Colucci et al, 2002;Wang et al, 2002;Heinemann et al, 2003;Scheithauer et al, 2003;Li and Chao, 2004;Ohkawa, 2004;Rocha Lima et al, 2004;Viret et al, 2004;Cunningham et al, 2005 Cullinan 1990 Cullinan 1990 Cullinan 1990 …”
Section: Gemcitabine Vs Gemcitabine-based Combination Chemotherapymentioning
confidence: 99%
“…Recent clinical trials using novel drug combinations have demonstrated some benefit, [2][3][4] but nevertheless, the overall 5-year survival rate for pancreatic cancer patients has remained low [2,3]. These poor outcomes have been attributed to many factors, including extensive fibrosis typically surrounding the pancreatic tumor.…”
Section: Introductionmentioning
confidence: 99%